Midwives or gravediggers of democracy?: the military’s impact on democratic development - Kühn, David (Democratization, 2017)
The political role of the military and its impact on the emergence, persistence and consolidation of new democracies has generated a large body of scholarship. In the light of military coups in a number of Third Wave democracies such as Ecuador (2000), Thailand (2006 and 2014), Honduras (2006) and Mali (2012), the return to electoral competition in a number of military-dominated regimes, and the military’s pivotal role during the Arab Spring, this research has recently focused on the forms, reasons and consequences of military contestation on democratic development. This special issue contributes to this recent scholarship by analysing both the potentially beneficial as well as the deleterious implications of military contestation on democratic transitions, quality and persistence in different world regions. This article introduces the special issue by providing a broader context for the four individual contributions and relates their findings to the recent theoretical and empirical literature on the military’s role as a midwife or gravedigger of democracy.
Gesehen am 27.11.2018